2015
DOI: 10.1109/tnb.2015.2430753
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Low Level Detection of L-Histidine Using Solution-Processed ZnO Nanorod on Flexible Substrate

Abstract: This work demonstrates a novel label free and sensitive approach for the detection of L-histidine. This is a simple and reliable method for ultra-low level detection of L-histidine. All solution processed synthesizing technique was utilized to develop such type of detection scheme. Silicon substrate was replaced by normal transparent sheet to make it more facile and cost-effective detection technique. Fabricated device for L-histidine detection works upon the variation of current through the ZnO nanorod with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Easy and reliable drop casting technique was utilized to fabricate humidity sensor. Our fabricated device quickly detects the environmental humidity by the electrical method [28] [29]. The response of the humidity detection was measured in terms of output current or conductance variation with the exposure of different levels of humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Easy and reliable drop casting technique was utilized to fabricate humidity sensor. Our fabricated device quickly detects the environmental humidity by the electrical method [28] [29]. The response of the humidity detection was measured in terms of output current or conductance variation with the exposure of different levels of humidity.…”
Section: Discussionmentioning
confidence: 99%
“…L-histidine (L-His) is an important composition for brain peptides and of muscle proteins (Nan et al, 1999 ; Rawat and Kailasa, 2014 ). It has been reported that the under-expression or over-expression of L-His may cause many diseases, like Friedreich ataxia, Parkinson's disease, chronic kidney disease, and psychological disorder (Sasmal et al, 2015 ). A SiO 2 PhC array was embedded in the hydrogel with L-His imprinted.…”
Section: Application In Human Healthmentioning
confidence: 99%
“…It often serves as a precursor for many chemicals and is extensively used in many fields, such as food, pharmaceutical, and feed industries. Moreover, it has an important implication upon several biological activities, e.g., transmission of metal elements in biological bases and neurotransmitting or neuromodulating in the mammalian central nervous system. , …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has an important implication upon several biological activities, e.g., transmission of metal elements in biological bases and neurotransmitting or neuromodulating in the mammalian central nervous system. 19,20 L-his is known to crystallize in two forms: A and B, with form A being stable. 20−27 Madden et al first reported the crystal structures of form A and form B in 1972.…”
Section: Introductionmentioning
confidence: 99%